Eculizumab Pharmacokinetics and Pharmacodynamics in Patients With Generalized Myasthenia Gravis - Monteleone, Jonathan P. R.; Gao, Xiang; Kleijn, Huub Jan; Bellanti, Francesco; Pelto, Ryan (Frontiers in Neurology, 2021)
Objective: To investigate the pharmacokinetics, pharmacodynamics, and exposure–response of the approved 900/1200 mg dosing regimen for the terminal complement C5 inhibitor eculizumab in patients with generalized myasthenia gravis (gMG). Methods: The analysis used data from 62 patients aged ≥18 years with anti-acetylcholine receptor (AChR) antibody-positive refractory gMG who received eculizumab during the REGAIN study (ClinicalTrials.gov: NCT01997229). One- and two-compartment population-pharmacokinetic models were evaluated, and the impact of covariates on pharmacokinetic parameters assessed. Relationships between eculizumab exposure and free complement protein 5 (C5) concentration, in vitro hemolytic activity, clinical response, and tolerability were characterized. Results: Steady-state serum eculizumab concentrations were achieved by Week 4 and were sustained throughout the 26-week treatment period. The eculizumab pharmacokinetic data were well described by a two-compartment model with first-order elimination, including effects of body weight on pharmacokinetic parameters and plasma-exchange events on clearance. Complete inhibition of terminal complement was achieved in nearly all patients at the time of trough and peak eculizumab concentrations at all post-dose timepoints assessed (free C5 <0.5 μg/mL in 92% patients; in vitro hemolysis <20% in 87% patients). Serum eculizumab concentrations of ≥116 µg/mL achieved free C5 concentrations of <0.5 µg/mL. Clinical efficacy and tolerability were consistent across the eculizumab exposure range. Conclusions: Rigorous, quantitative, model-based exposure–response analysis of serum eculizumab concentration and response data demonstrated that the approved eculizumab dosing (900/1200 mg) for adults with anti-AChR antibody-positive refractory gMG rapidly achieved complete inhibition of terminal complement activation and provided sustained clinical efficacy across the eculizumab exposure range.